2002
DOI: 10.2307/3030230
|View full text |Cite
|
Sign up to set email alerts
|

Having an Abortion Using Mifepristone and Home Misoprostol: A Qualitative Analysis of Women's Experiences

Abstract: Learning whether women are concerned about personal control may help clinicians identify appropriate candidates for medical abortion. In addition, clinicians could help allay women's anxiety at their first abortion visit by explaining that the uncertainties posed by any medical procedure create similar feelings. Clinicians also should reemphasize at the follow-up visit that there are no long-term health effects related to abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
83
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 15 publications
(14 reference statements)
6
83
0
Order By: Relevance
“…In legal settings, we found that the older studies described more medicalized approaches that required women to remain in clinic for four hours following misoprostol administration. 16,17 Shifts to less medicalized care in the more recent studies took the following forms: administering the misoprostol to women at the second appointment but then sending them home to abort, [18][19][20]4 giving women misoprostol at the second appointment but allowing them to selfadminister it at home, 18,21 giving women misoprostol at the first appointment to be self-administered at home, 19,[22][23][24][25][26][27] and giving women both mifepristone and misoprostol at the first appointment to be taken at home. 27,28 The studies from legal settings that reported misoprostol-only abortions reported self-administration at home.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In legal settings, we found that the older studies described more medicalized approaches that required women to remain in clinic for four hours following misoprostol administration. 16,17 Shifts to less medicalized care in the more recent studies took the following forms: administering the misoprostol to women at the second appointment but then sending them home to abort, [18][19][20]4 giving women misoprostol at the second appointment but allowing them to selfadminister it at home, 18,21 giving women misoprostol at the first appointment to be self-administered at home, 19,[22][23][24][25][26][27] and giving women both mifepristone and misoprostol at the first appointment to be taken at home. 27,28 The studies from legal settings that reported misoprostol-only abortions reported self-administration at home.…”
Section: Resultsmentioning
confidence: 99%
“…They often reported some degree of anxiety at the beginning of the process but reported relief at the end and a strong sense of satisfaction with the choice to self-manage. 19,20,22,23,29 In some contexts, the use of misoprostol at home for early medical abortion falls within existing interpretive frameworks and practices (such as "menstrual regulation" (Bangladesh) and was understood as one of many treatments for local illness categories referring to missed menstrual periods (e.g. "late menses" in Brazil).…”
Section: General Perceptions Of Self-management Of Medical Abortionmentioning
confidence: 99%
See 3 more Smart Citations